(270 - х) - 46 = 56 522 - (х - 25) = 42
270 - х = 56 + 46 х - 25 = 522 - 42
270 - х = 102 х - 25 = 480
х = 270 - 102 х = 480 + 25
х = 168 х = 505
--------------------------------------------------------------------------------
(135 - х) + 45 = 67
135 - х = 67 - 45
135 - х = 22
х = 135 - 22
х = 113
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
(270 - х) - 46 = 56 522 - (х - 25) = 42
270 - х = 56 + 46 х - 25 = 522 - 42
270 - х = 102 х - 25 = 480
х = 270 - 102 х = 480 + 25
х = 168 х = 505
--------------------------------------------------------------------------------
(135 - х) + 45 = 67
135 - х = 67 - 45
135 - х = 22
х = 135 - 22
х = 113